Impact of reflux, bruxism, age, and plaque index on anterior tooth wear: A cross-sectional clinical evaluation (Annals of Medical Research, 2025)
Aim: This study aims to evaluate the effect of variables such as gastroesophageal reflux disease (GERD), bruxism, plaque index, and age on erosive wear occurring on the palatal surfaces of maxillary anterior teeth, and to objectively measure this wear using the Anterior Clinical Erosive Classification (ACEC).Materials and Methods: A total of 507 individuals were included. Participants completed self-report questionnaires regarding the presence, previous diagnosis, disease duration, and medication use. Bruxism was assessed through self-report and clinical examination. Erosive wear on maxillary anterior teeth palatal surfaces was measured using ACEC, and plaque accumulation using the Silness and Löe Plaque Index. Statistical analyses included independent sample t-tests and Spearman/Pearson correlation coefficients. Significance was set at p
Keywords: Gastroesophageal reflux disease; Dental erosion; Anterior clinical erosive classification; Tooth wear